The blessed hope papers on the Lord's coming and connected events - Dennett, Edward, 1831-1914 (Oak Park, IL Bible Truth, 1879)
Includes bibliographical references.
Papers first issued in "The Christian friend and instuctor". Brethren writer.
Keywords: Eschatology